A national survey of skin health in nursing personnel. (1st April 2022) - Parsons, V; Oxley, G; Hines, J; Gallagher, R; Sunley, K; Fellows, Caroline; Hodgkinson, M; Ormandy, K; Gould, D
Abstract: Background: Hand dermatitis is a well-established occupational risk in nursing staff. Aims: To explore skin health in nursing staff and to develop resources and recommendations to promote good skincare at work. Methods: Cross-sectional survey. Results: We analysed data from 1, 545 surveys. Forty-six percent reported 'poor' skin health and the majority (93%) experienced at least one skin problem over the previous 12 months, with only 22% seeking help from their employer. Only 2% took time off work due to skin problems, with many expressing concerns that taking sick leave would be viewed negatively by others. Over half (53%) had reduced or stopped using antibacterial rubs and soap, and 18% had reduced the use of gloves. Most respondents used hand cream and over half used products they had purchased themselves. Only 42% received skin health care information from employers, with fewer (26%) receiving training on how to identify early signs of skin disease. Only 16% had access to skin surveillance in line with regulatory requirements. Only 26% of respondents were aware of the support offered by their professional nursing association. Suggestions for improving skin health included increasing publicity concerning the importance of skin health in healthcare settings, improving access to hand creams, better quality products, enhanced education and training and more involvement from Occupational Health (OH). Conclusions: Results confirm that poor skin health remains a persistent problem for nurses. Employers could do more to promote skin health and nurses need to be made more aware of the support and guidance offered by professional bodies.